Kommunen im Klimawandel Best Practices als Chance zur grünen Transformation? - Nagorny-Koring , Nanja (Urban Studies, 2018)
How can you redesign cities effectively and quickly in a climate-friendly way? The exchange of knowledge between municipalities as well as the imitation of good practices is the key to »green transformation«. Using the example of "best practice" government technology, Nanja Nagorny-Koring fundamentally questions the widespread belief in the "principle of imitation" and paints a picture of why best practices are so popular despite the apparent dissociation of claim and reality. It presents in detail how best practices in communal climate protection are created, disseminated and applied.